2021
DOI: 10.1177/1079063221993478
|View full text |Cite
|
Sign up to set email alerts
|

Is There an “Expert” Stranger Rapist?

Abstract: The concept of expertise applied to the criminal context assumes that offenders are driven by the abilities to both maximize the payoffs and minimize the risks associated with the crime-commission. This study tested the articulation between these two types of decisions taken by stranger rapists to successfully commit their crime. Specifically, this study aims to identify whether offenders whose modus operandi is indicative of criminal expertise are more likely to use forensic awareness strategies. Multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 85 publications
3
41
1
2
Order By: Relevance
“…Moreover, destroying or removing evidence is a sophisticated strategy used by those who have prior offense experience (e.g., Davies et al, 1997) and is an indication of expertise in detection avoidance (e.g., Reale et al, 2020). Furthermore, the crime-commission process of sexual burglary in the current study closely resembles the "expert rape" identified by (Chopin et al, 2021) who had sophisticated modus operandi's and used various forensic awareness strategies to avoid detection. Moreover, Park et al (2008) found that forensic awareness was a strategy used by criminally sophisticated persons who committed serial sexual offenses.…”
Section: Crime and Post-crime Phasesmentioning
confidence: 65%
See 2 more Smart Citations
“…Moreover, destroying or removing evidence is a sophisticated strategy used by those who have prior offense experience (e.g., Davies et al, 1997) and is an indication of expertise in detection avoidance (e.g., Reale et al, 2020). Furthermore, the crime-commission process of sexual burglary in the current study closely resembles the "expert rape" identified by (Chopin et al, 2021) who had sophisticated modus operandi's and used various forensic awareness strategies to avoid detection. Moreover, Park et al (2008) found that forensic awareness was a strategy used by criminally sophisticated persons who committed serial sexual offenses.…”
Section: Crime and Post-crime Phasesmentioning
confidence: 65%
“…The first subcategory includes eight variables related to POs and victim characteristics. Victim variables were selected because previous studies have shown that more criminally sophisticated persons tend to target their victims, especially those who are from a vulnerable population (e.g., Beauregard & Proulx, 2017;Chopin et al, 2021;Wright & Decker, 2002). Characteristics for POs were included based on previous studies that suggest criminally sophisticated persons with sexual offenses will be older, socially adept, and have a history of previous offenses (e.g., Bourke et al, 2012;Ward, 1999).…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there has been considerable variation in the application of the expertise framework to offending populations, one aspect that is widely agreed upon is that criminal expertise is best represented as a continuum novice to expert (e.g., Bourke et al, 2012;Chopin et al, 2021;Nee & Ward, 2015;Ward, 1999). In the field of sexual offending, a continuum of expertise has been observed in child sexual offending domains (Bourke et al, 2012) as well as adult rape (Chopin et al, 2021). These studies have found support for a novice to expert continuum, showing that more "expert" offenders possessed superior offense skills and knowledge, especially pertaining to detection avoidance, and gaining victim compliance and control (Bourke et al, 2012;Chopin et al, 2021).…”
Section: Continuum Of Expertisementioning
confidence: 99%
“…Although several advancements to the expertise literature have been made through an examination of burglary (see Nee, 2015 for a review), and more recently in sexual offending (Bourke et al, 2012;Chopin et al, 2021), more complex crimes such as those that combine two specific types of offenses (i.e., a hybrid offense) have been largely overlooked in both the criminal expertise literature and in criminological studies more generally (Beauregard & Chopin, 2020). In the first study of criminal expertise on hybrid offenders, Reale et al (in press) showed that the crime-commission process of sexual burglary (i.e., break-and entering, theft, and sexual assault offense) involved more "domain-specific" expertise in detection avoidance, compared with sexual robbery (i.e., personal theft and sexual assault offense), but also found similar skills related to target appraisal between these two offenses, suggesting these offenses may also share an "overlapping expertise" or "transferable" expertise (Nee et al, 2019) related to violent offending.…”
mentioning
confidence: 99%